Descriptions of two new species of the genus Paragus Latreille (Diptera: Syrphidae), with a key to males of all South African species - Tot, Tamara; Radenković, Snežana; Nedeljković, Zorica; Likov, Laura; Vujić, Ante (Zootaxa, 2020)
Two new species of the genus Paragus Latreille, 1804 are described from the Republic of South Africa: Paragus longipilus Tot, Vujić et Radenković sp. nov. and Paragus megacercus Tot, Vujić et Radenković sp. nov. These new species belong to the subgenus Pandasyopthalmus Stuckenberg, 1954a. Paragus longipilus sp. nov. is a member of the P. jozanus group, whereas Paragus megacercus sp. nov. belongs to the P. tibialis group. The taxonomic status of Paragus chalybeatus Hull, 1964 is revised and proposed as synonym of Paragus punctatus Hull, 1949. Additionally, an identification key to males of the South African species of Paragus is provided. Results of the present study confirm a significant level of endemism of Paragus in the Afrotropical Region (12 out of 29).